2003
DOI: 10.5914/tropocean.v31i2.5023
|View full text |Cite
|
Sign up to set email alerts
|

Disponibilidade Nutricional da Bacia do Pina e Rio Tejipió (Recife-PE-Brasil) em Relação aos Nutrientes e Biomassa Primária (Setembro/2000)

Abstract: RESUMOO presente trabalho foi desenvolvido na Bacia do Pina-PE cuja área estuarina está situada na parte interna do Porto do Recife, em plena zona urbana. É formada pela confluência dos rios Tejipió, Jiquiá, Jordão, Pina e pelo braço sul do Capibaribe. O trabalho teve como objetivo analisar a dinâmica desta bacia em relação à salinidade, determinar o comportamento conservativo ou não conservativo dos nutrientes, registrando a disponibilidade nutricional e o desenvolvimento da população fitoplanctônica através … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 2 publications
2
11
0
4
Order By: Relevance
“…At the Pina Basin, salinity varied according to precipitation and were higher during the dry season and at point 1. Feitosa et al (1999), Nascimento et al (2003) and Noriega et al (2005) found similar values to those recorded by this study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…At the Pina Basin, salinity varied according to precipitation and were higher during the dry season and at point 1. Feitosa et al (1999), Nascimento et al (2003) and Noriega et al (2005) found similar values to those recorded by this study.…”
Section: Discussionsupporting
confidence: 92%
“…The characteristically alkaline pH observed during the study period agrees with the results reported by Feitosa et al (1999) and Nascimento et al (2003) for the same area. According to Trabulsi et al (2005), coliforms develop within a wide pH range, from 4.4 to 9.0.…”
Section: Discussionsupporting
confidence: 90%
“…This species tolerates a wide range of salinity. However, the highest numbers occur in low salinities, showing that there are other factors influencing the presence of this genus (NCHE-FAMBO et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is within the limits for marine life (NASCIMENTO et al, 2003). The renewal time of Bacanga River Estuary waters depends on the seasonality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation